Insulin resistance in Chinese patients with type 2 diabetes is associated with C-reactive protein independent of abdominal obesity - Lu, Bin (BioMed Central, 2010)
BACKGROUND: There is debate as to whether the association between C-reactive protein (CRP) and insulin resistance is independent of body fatness, particularly central obesity. Therefore, the association among CRP, insulin resistance and obesity was analyzed in Chinese patients with type 2 diabetes. METHODS: The study included 520 Chinese patients diagnosed with type 2 diabetes with CRP levels not exceeding 10 mg/L. The degree of insulin resistance was determined with the homeostasis model assessment of insulin resistance (HOMA-IR). The CRP levels were categorized into quartiles from the lowest to the highest concentrations (Q1-Q4). RESULTS: Body mass index (BMI) and waist circumference (WC) were both higher in Q4, Q3 and Q2 than those in Q1. HOMA-IR was higher in Q2, Q3 and Q4 than that in Q1 (Q1 vs Q4, P < 0.001; Q1 vs Q3, P < 0.001; Q1 vs Q2, P = 0.028). Log CRP was significantly correlated with log HOMA-IR (correlation coefficient: 0.230, P < 0.001) and BMI (correlation coefficient: 0.305, P < 0.001) and WC (correlation coefficient: 0.240, P < 0.001) by Spearman correlation analysis. Multiple linear regression analysis adjusting for age, gender and components of metabolic syndrome, log CRP was also independently associated with log HOMA-IR (β coefficient, 0.168; P < 0.001) and WC (β coefficient, 0.131; P = 0.006). CONCLUSION: These findings showed that insulin resistance was associated with CRP levels independent of abdominal obesity in Chinese patients with type 2 diabetes, suggesting that abdominal obesity could only partly explain the link between subclinical inflammation and insulin resistance.